2014
DOI: 10.1002/ijc.28810
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous NF‐κB inhibition and E‐cadherin upregulation mediate mutually synergistic anticancer activity of celastrol and SAHA in vitro and in vivo

Abstract: Suberoylanilide hydroxamic acid (SAHA) is a promising histone deacetylase (HDAC) inhibitor approved by the US Food and Drug Administration (FDA) and whose clinical application for solid tumours is partially limited by decreased susceptibility in cancer cells due to nuclear factor (NF)-jB activation. As an NF-jB inhibitor, celastrol exhibits potent anticancer effects but has failed to enter clinical trials due to its toxicity. In this report, we demonstrated that the combination of celastrol and SAHA exerted su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 51 publications
2
36
0
Order By: Relevance
“…Theoretically, SAHA facilitates the accumulation of acetylated cellular proteins such as histones and transcription factors, and thus induces the dynamic changes of gene expression in tumor cells. Unfortunately, the extensive clinical trials suggest that SAHA might be sometimes ineffective on certain solid tumors [35]. …”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, SAHA facilitates the accumulation of acetylated cellular proteins such as histones and transcription factors, and thus induces the dynamic changes of gene expression in tumor cells. Unfortunately, the extensive clinical trials suggest that SAHA might be sometimes ineffective on certain solid tumors [35]. …”
Section: Introductionmentioning
confidence: 99%
“…Clinical application of celastrol is rather limited because of its poor solubility and narrow therapeutic window (Zheng et al., ). However, combined therapy of low doses of celastrol with other agents could represent a novel, efficient strategy with acceptable toxicity to treat cancer (Chen et al., ; Zheng et al., ). These data suggest potential avenues to be explored in future also for neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…SAHA arrests cancer cell growth by inhibiting classes I and II zinc‐binding HDACs . Substantial evidence indicated that SAHA induced histone acetylation in transcription factor complexes that regulate the genetic expression of molecules associated with malignant phenotypes . Similar to HDACi, ING5 may form MOZ/MORF‐BRPF1/2/3‐ING5‐hEaf6 and JADE1/2/3‐HBO1‐ING4/5‐hEaf6 HAT complexes to acetylate histones H3 and H4, respectively …”
Section: Introductionmentioning
confidence: 99%
“…5,6 Substantial evidence indicated that SAHA induced histone acetylation in transcription factor complexes that regulate the genetic expression of molecules associated with malignant phenotypes. 7 Similar to HDACi, ING5 may form MOZ/ MORF-BRPF1/2/3-ING5-hEaf6 and JADE1/2/3-HBO1-ING4/5-hEaf6 HAT complexes to acetylate histones H3 and H4, respectively. 8 Suberoylanilide hydroxamic acid suppresses the growth of HeLa cells and induces apoptosis, which is accompanied by PARP cleavage, Caspase-3 activation, potential loss of the mitochondrial membrane, and ROS generation.…”
mentioning
confidence: 99%